Writer’s Block:: a reflective literature review - Evans, Kate (European Journal for Qualitative Research in Psychotherapy, 2011)
For a significant proportion of therapists, the mere thought of writing up research academically and then perhaps striving to publish any writings is anxiety provoking. These therapists may be suffering from ‘Writer’s Block’ – a process, I suggest, that gets in the way of meaningful and relevant research being completed by practitioners which could help inform and develop our way of working. Through this review of the literature on Writer’s Block, intertwined by personal reflections on my own experience, I aim to explore possible causes and offer some tentative solutions.